K44M ferritic stainless steel as possible interconnect material for SOFC stack operating at 600 °C: Characterization of the oxidation behaviour at early working stages. (9th March 2015) - Piccardo, Paolo; Anelli, Simone; Bongiorno, Valeria; Spotorno, Roberto; Repetto, Luca; Girardon, Pauline
Abstract: A commercial ferritic stainless steel (FSS) known as K44M (Type 444, according to ASTM A 240, DIN 1.4521 according to NF EN 10088-2) was aged in static air in two differing thicknesses (i.e. 1.5 and 0.4 mm) at a thermal cycle corresponding to the curing phase of an experimental glass used as sealing in solid oxide fuel cell (SOFC) stacks, and to an ageing process in air of 200 h at 600 °C. The characterization performed on the aged samples after the complete treatment and at each step of the thermal cycle allowed to investigate the scale formed depending on the temperature and to the thickness of the samples. Highlights: Oxidation behaviour of stainless steel K44M at various temperatures. Stability of thermal grown oxides. Relationship between thickness and scale characteristics.